Physical therapy and occupational therapy in Parkinson's disease. (3rd October 2017) - Radder, Danique L.M.; Sturkenboom, Ingrid H.; van Nimwegen, Marlies; Keus, Samyra H.; Bloem, Bastiaan R.; de Vries, Nienke M.
ABSTRACT: Current medical management is only partially effective in controlling the symptoms of Parkinson's disease. As part of comprehensive multidisciplinary care, physical therapy and occupational therapy aim to support people with Parkinson's disease in dealing with the consequences of their disease in daily activities. In this narrative review, we address the limitations that people with Parkinson's disease may encounter despite optimal medical management, and we clarify both the unique and shared approaches that physical therapists and occupational therapists can apply in treating these limitations.